Fibronectin splice variation in human knee cartilage, meniscus and synovial membrane: Observations in osteoarthritic knee. Issue 4 (6th January 2015) - Scanzello, Carla R.; Markova, Dessislava Z.; Chee, Ana; Xiu, Yan; Adams, Sherrill L.; Anderson, Greg; Zgonis, Miltiadis; Qin, Ling; An, Howard S.; Zhang, Yejia
ABSTRACT: Fibronectin (FN) is a widely expressed molecule that can participate in development of osteoarthritis (OA) affecting cartilage, meniscus, and synovial membrane (SM). The alternatively spliced isoforms of FN in joint tissues other than cartilage have not been extensively studied previously. The present study compares FN splice variation in patients with varying degrees of osteoarthritic change. Joint tissues were collected from asymptomatic donors and patients undergoing arthroscopic procedures. Total RNA was amplified by PCR using primers flanking alternatively spliced Extra Domain A (EDA), Extra Domain B (EDB) and Variable (V) regions. EDB +, EDB − and EDA − and V + variants were present in all joint tissues, while the EDA + variant was rarely detected. Expression levels of EDB + and EDV + variants were similar in cartilage, synovium, and meniscal tissues. Synovial expression of V + FN in arthroscopy patients varied with degree of cartilage degeneration. Two V − isoforms, previously identified in cartilage, were also present in SM and meniscus. Fibronectin splicing in meniscus and SM bears striking resemblance to that of cartilage. Expression levels of synovial V + FN varied with degree of cartilage degeneration. V + FN should be investigated as a potential biomarker of disease stage or progression in larger populations. © 2015 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 33:556–562, 2015.